Pembuatan Vidio Iklan Animasi Menggunakan After Efect Untuk Meningkatkan Brand Awareness pada Buket Dikala - Hidayati, Nurul Sipa; Abdullah, Fahmi; Anggraini, Novita (Melati Institute, 2023)
The use of video advertisements as a marketing medium is becoming increasingly popular in the current digital era. Small companies or start-ups can leverage animated video ads to promote their products at a more affordable cost compared to traditional video ad production. The objective of this research is to create an animated video advertisement using After Effects to enhance brand awareness for Buket Dikala, a flower company in Bandung. The results of this study indicate that the animated video ad created by the author can improve brand awareness for Buket Dikala. The author recommends the use of animated video ads for small companies or start-ups aiming to enhance their marketing effectiveness. Several factors that need to be considered in creating an effective animated video ad include aligning the ad's style and tone with the target audience, paying attention to the visual and audio quality of the ad, determining the appropriate duration, and including a clear call to action. By utilizing animated video ads, small companies or start-ups can effectively and affordably expand their market reach.